Effect of Network Topology on the Performance of ADMM-Based SVMs - Tavara, Shirin; Schliep, Alexander (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
Alternating Direction Method Of Multipliers (ADMM) is one of the promising frameworks for training Support Vector Machines (SVMs) on large-scale data in a distributed manner. In a consensus-based ADMM, nodes may only communicate with one-hop neighbors and this may cause slow convergence. In this paper, we investigate the impact of network topology on the convergence speed of ADMM-based SVMs using expander graphs. In particular, we investigate how much the expansion property of the network influence the convergence and which topology is preferable. Besides, we supply an implementation making these theoretical advances practically available. The results of the experiments show that graphs with large spectral gaps and higher degrees exhibit accelerated convergence.